(3aJM GdQMef aj JLhjO GdbQBfs
(3ChdgG (B:s
(3hHYO agPg QSGdI JJYdb HJLhjO GdbQBf GdYXje aUd aj GdEXgGQ CYde Cf Gdfhf GdSGcfI hGdJfhjf s
(3BNQgG (B:s
(3hef GdeWhdGJ GdEJMGa hTQM GdTGWHjI dCHj TGeI hef eNJUQGJ GdeMGfj aj GdJLhjO hZjQgG ef GdeYJeOGJ hfSCd Gddg Cf jfaYfG HgG Cejf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
(3GdfSNI HgG JdhjK s
Keywords: (3GdbQGAGJ hGdJLhjOs